Deoxyribonucleic Acid Synthesis in Root Cap Cells of Cultured Roots of Convolvulus - Phillips, Harry L. (1971)
Isolated cultured roots of Convolvulus arvensis L. were incubated in 0.2 microcurie per milliliter methyl-(3)H-thymidine for 14 hours, for 64 hours, or for 14 hours followed by transfer to fresh nutrient medium without tritiated thymidine. Autoradiographs of serial, longitudinal sections of roots which were continuously incubated with tritiated thymidine showed that cells of the root cap columella did not undergo DNA synthesis after their formation from the root cap initials. In roots pulse-labeled with tritiated thymidine, the movement of labeled cells through the root cap columella was followed. Labeled cells were displaced at a constant rate of 72 microns per day over a period of 6 to 9 days before they were sloughed off from the root cap. The specialized role of the root cap cells in relation to their distinctive metabolism and longevity is discussed.